Determinan Pendapatan Driver Maxim Bike Di Kota Bandar Lampung - Adi Pratama, Arya; Budiarty, Ida (Shofanah Media Berkah, 2025)
Through a descriptive approach, this study analyzes the extent to which average fares, travel intensity (trips), and fixed cost components and operational costs affect the income of Maxim drivers in the Bandar Lampung City area. This study relies on primary data obtained from the distribution of questionnaires through structured interviews with 50 drivers, who were selected using the purposive sampling method. Data processing and analysis is done with the help of Eviews 13 software using multiple linear regression methods. The findings from this study use that partially, the four variables are average rates, number of trips, fixed costs, and variable costs have a positive and significant influence on the income received by Maxim drivers. Together, variable average rates, number of trips, fixed costs, and variable costs have a significant impact on driver income.